HIF1α inhibitor 2-methoxyestradiol decreases NRN1 expression and represses in vivo and in vitro growth of patient-derived testicular germ cell tumor spheroids. (1st October 2020) - Namekawa, Takeshi; Kitayama, Sachi; Ikeda, Kazuhiro; Horie-Inoue, Kuniko; Suzuki, Takashi; Okamoto, Koji; Ichikawa, Tomohiko; Yano, Akihiro; Kawakami, Satoru; Inoue, Satoshi
Abstract: Testicular germ cell tumor (GCT) is the most common type of malignancy in young males. Patients with nonseminomatous GCT still have poor prognosis. To identify new therapeutic targets, we generated patient-derived cells (PDCs) and their xenograft (PDCX) models from 3 distinct GCT patients' specimens. The pathological features of GCT PDCs and PDCX tumors recapitulated those of nonseminomatous components exhibiting in the corresponding patients' specimens. Notably, stemness-related markers and hypoxia-related genes, including hypoxia inducible factor 1α (HIF1A) and neuritin 1 (NRN1), were abundantly expressed in three-dimensional spheroid cultures of GCT PDCs. We identified functional HIF1α response elements in the NRN1 promoter and defined that their transcriptional activities were substantially activated by hypoxia. HIF1α inhibition by siRNAs or an inhibitor, 2-methoxyestradiol, significantly suppressed NRN1 expression and decreased the in vitro and in vivo growth of PDC spheroids. Moreover, NRN1 knockdown efficiently suppressed PDC proliferation. These results suggest that HIF1α and NRN1 are potential diagnostic and therapeutic targets, and that 2-methoxyestradiol could be applied to clinical management of GCT. Overall, our GCT PDC and PDCX models would be useful as preclinical models for precision medicine targeting each patient. Highlights: Patient-derived testicular germ cell tumor (GCT) models were established. Stemness- and hypoxia-related genes were highly expressed in GCT spheroids. HIF1A transcriptionally controls NRN1 expression. NRN1 was abundantly expressed in nonseminomatous GCT. Inhibition of HIF1A and NRN1 suppressed GCT proliferation.